Maximally spaced projection sequencing in electron paramagnetic resonance imaging. Issue 1 (24th June 2015) - Redler, Gage; Epel, Boris; Halpern, Howard J.
ABSTRACT: Electron paramagnetic resonance imaging (EPRI) provides 3D images of absolute oxygen concentration (pO2 ) in vivo with excellent spatial and pO2 resolution. When investigating such physiologic parameters in living animals, the situation is inherently dynamic. Improvements in temporal resolution and experimental versatility are necessary to properly study such a system. Uniformly distributed projections result in efficient use of data for image reconstruction. This has dictated current methods such as equal‐solid‐angle (ESA) spacing of projections. However, acquisition sequencing must still be optimized to achieve uniformity throughout imaging. An object‐independent method for uniform acquisition of projections, using the ESA uniform distribution for the final set of projections, is presented. Each successive projection maximizes the distance in the gradient space between itself and prior projections. This maximally spaced projection sequencing (MSPS) method improves image quality for intermediate images reconstructed from incomplete projection sets, enabling useful real‐time reconstruction. This method also provides improved experimental versatility, reduced artifacts, and the ability to adjust temporal resolution post factum to best fit the data and its application. The MSPS method in EPRI provides the improvements necessary to more appropriately study a dynamic system. © 2015 Wiley Periodicals, Inc. Concepts Magn Reson Part B (Magn Reson Engineering) 45B: 33–45, 2015